2005
DOI: 10.1029/2005ja011093
|View full text |Cite
|
Sign up to set email alerts
|

Source of Pc4 pulsations observed on the nightside

Abstract: We have studied magnetic pulsations in the 5‐ to 20‐mHz (Pc4) band observed on 7 January 1997 from ∼1400 UT to ∼1600 UT at ground stations located on the nightside. At low latitudes (L < 2) the spectral content of the pulsations did not differ much from the Pi2 pulsations that were observed adjacent to the above interval. However, during the Pc4 event the auroral luminosity measured by the Ultra Violet Imager instrument on the Polar spacecraft was steadily declining toward a very low level. Also, the Geotail s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 55 publications
3
24
1
Order By: Relevance
“…In fact, there is observational evidence for a dayside plasmaspheric cavity mode (Takahashi et al 2009) and its propagation to the night side (Takahashi et al 2005). Studies of such events could shed light on the role the plasmasphere commonly plays in trapping fast mode waves.…”
Section: Longitudinal Structurementioning
confidence: 98%
See 1 more Smart Citation
“…In fact, there is observational evidence for a dayside plasmaspheric cavity mode (Takahashi et al 2009) and its propagation to the night side (Takahashi et al 2005). Studies of such events could shed light on the role the plasmasphere commonly plays in trapping fast mode waves.…”
Section: Longitudinal Structurementioning
confidence: 98%
“…However, spacecraft observations of Pi2 pulsations in the dayside magnetosphere is challenging because they are easily masked by Pc4 pulsations driven by the solar wind pressure variations (Takahashi et al 2005) or by transmission of upstream waves into the magnetosphere (Heilig et al 2007). Only on rare occasions dayside Pi2 pulsations have been reported from spacecraft observations in the magnetosphere: at L ∼ 6 in the equatorial magnetosphere and at a LEO satellite (Han et al 2004).…”
Section: Longitudinal Structurementioning
confidence: 99%
“…Pc4 (7–25 mHz) ULF waves are abundant on the dayside [e.g., Chi et al , , ; Kim and Takahashi , ] and occasionally observed on the nightside [ Takahashi et al , ]. Poloidal waves in the Pc4 band have been noticed to correspond to the highly monochromatic and large‐amplitude “giant pulsations” on the ground.…”
Section: Introductionmentioning
confidence: 99%
“…Typical period of low-latitude Pi2 pulsations, from a fraction of a minute to few minutes, is believed to be determined either by eigenperiod of the plasmasphere cavity mode (Sutcliffe et al 2013) or by a forced response to a periodic energy release in the magnetotail (Keiling and Takahashi 2011). Takahashi et al (2005) analyzed nightside Pc4s and Pi2s and found that these two types of ULF waves were generated by different physical mechanisms, although their central frequencies were close.…”
Section: Introductionmentioning
confidence: 99%